Analysis of plastic debris on Malaysia beaches / Liyana 'Izzati Aris - Liyana 'Izzati, Aris (2012)
Plastic debris is the main cluster of solid waste component present in the marine environment. Anthropogenic activities namely recreational and fishing activities are believed to contribute to the abundance of plastic debris (1 – 30 mm in size) especially along the beach. This study was undertaken to quantify and assess the degree of plastic debris buried in sand according to size with a view to classify such debris deposition at some Malaysian beaches. Another objective, the abundance distribution of the buried plastics was also studied in relation to the tidal zones of the beaches. Six selected beaches (in three different states of Malaysia) served as the representative of the fishing and recreational beaches in this study namely; Teluk Kemang Beach, Pasir Panjang Beach, Batu Burok Beach, Seberang Takir Beach, Tanjung Aru Beach and Teluk Likas Beach. Plastic debris were sampled once a month for three consecutive months. At each beach, triplicates of 12.5 L of sand samples were collected from different tidal zones.